Foreign Relations of the Khorezm People of Soviet Republic and its Study in the Abroad - Navruzbek Shokhnazarovich, Rakhimov (International Journal of Psychosocial Rehabilitation, 2020)
The history of Uzbek statehood in the twentieth century is one of the periods that require in-depth study. For a century, in addition to Uzbekistan, many scientific studies have been conducted in foreign countries on the abolition of the Khiva Khanate and the history of the Khorezm People of the Soviet Republic. As a result, information and archival documents on the subject were put into scientific circulation. At the same time, this period in the history of our statehood was complex and controversial, and ideological pressures prevailed in the scientific study of the problem. The foreign relations of the Khorezm People’s Soviet Republic and its study abroad play an important role in the real creation of this period of the statehood of Uzbekistan. Because foreign researchers have different approaches to the issue, depending on their place of residence and socio-cultural environment, they have tried to cover the issue in the "anti-communist spirit." In some places, the role of Russian communists in the formation of the Khorezm People’s Soviet Republic is exaggerated, and the services of local people’s representatives are not sufficiently recognized, and sometimes the opposite is true. This allows for a comparative study of these issues. The article emphasizes these issues.